Manejo do consórcio com culturas de adubação verde em sistema plantio direto - Reis, Gustavo Naves Dos [UNESP]; Silva, Rouverson Pereira Da [UNESP]; Furlani, Carlos Eduardo Angeli [UNESP]; Cavalin Neto, Júlio [UNESP]; Grotta, Danilo César Checchio [UNESP]; Cortez, Jorge Wilson [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2007)
The present research aimed to study the influence of 3 managements in the production of dry matter in 2 intercrops of vegetal cover, in experiment realized in the area of the Laboratory of Machines and Agricultural Mechanization (LAMMA), of the Department of Rural Engeneering, FCAV/Unesp, Jaboticabal, state of São Paulo. The intercrops of vegetal cover utilized were: Crotalaria juncea + Cajanus cajan and Stilozobium niveum + Cajanus cajan, managed under 3 different systems: straw grinders, cleared and herbicide, in randomized block design arranged in a 2x3 factorial, with 4 replications, totalizing 24 portions. The parameters evaluated were: dry matter of the intercrops at 30, 60, 97 and 125 days after sowing and dry matter after management at 30, 51 e 71 days together with displacement speed and effective field capacity of each group. The analyses showed that the managements did not affect the production of dry matter on the aerial part of the intercrops. At 30, 97 and 125 days after sowing (DAS) and at 30 days after management (DAM) the crops managed with straw grinder presented higher dry matter. The displacement speed and the effective field capacity presented statistical difference.

Este trabalho objetivou estudar a influência de três manejos na produção de massa seca de dois consórcios de coberturas vegetais, em experimento realizado em área experimental do Laboratório de Máquinas e Mecanização Agrícola (LAMMA), do Departamento de Engenharia Rural, FCAV/Unesp, Jaboticabal, Estado de São Paulo. Os consórcios de coberturas vegetais utilizados foram: Crotalaria + Guandu e Mucuna + Guandu, manejados sob três diferentes sistemas: Triturador de palhas; Roçadora e Herbicida, em delineamento em blocos ao acaso e esquema fatorial 2x3, com 4 repetições, totalizando 24 parcelas. Foram avaliados os seguintes parâmetros: massa seca dos consórcios, aos 30, 60, 97 e 125 dias após a semeadura das espécies, a massa seca após o manejo, aos 30, 51 e 71 dias, juntamente com a velocidade de deslocamento e a capacidade de campo efetiva de cada conjunto. As análises permitiram verificar que os manejos não afetaram a produção de massa seca da parte aérea dos consórcios. Aos 30, 97 e 125 dias após a semeadura (DAS) e aos 30 dias após o manejo (DAM), as culturas manejadas com triturador de palhas apresentaram maior quantidade de massa seca. A velocidade de deslocamento e capacidade de campo efetiva apresentaram diferença estatística.
Intercrop management with green manure crops in no tillage system
Keywords: Crotalaria juncea; Stilozobium niveum; Cajanus cajan; Crotalaria juncea; Stilozobium niveum; Cajanus cajan